Radio telemetry of the Valcheta frog Pleurodema somuncurense: study of spatial ecology and home range in a Critically Endangered species - Calvo, Rodrigo (2025)
This study represents the first application of radio telemetry on the Critically Endangered Valcheta frog Pleurodemasomuncurense from Argentina’s Patagonia, aimed at understanding its spatial ecology, daily movements andhome range. Six adult individuals were equipped with radio transmitters to assess their activity patterns and habitat use.Average travel distances from sunset to night detection and from sunset to sunrise were 6.47 m (± 4.2) and 6.32 m (±4.87), respectively, with no significant difference (Student’s t-test, p = 0.42, α = 0.05). Over a complete activity cycle,individuals moved an average of 8.62 metres (SD = 2.2). The estimated home range was 39 m² including an individual withheightened movement, and 30 m² excluding it. Movements ≤ 5 m were categorised as local adjustments, while > 5m were exploratory migrations, the latter comprising 25.54% of movements in most individuals, though one frog exhibited 56.25%. Despite successful data collection, high mortality and transmitter displacement highlight the technique’s limitations in aquatic anurans. Findings from this study provide valuable data on P. somuncurense’s habitat connectivity needs, informing restoration and onservation efforts across its restricted range. Future studies should consider adjusting the telemetry approach to mitigate the impact on behaviour and survival.